2001
DOI: 10.1038/oby.2001.137
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a Primary Care Physician Network Obesity Management Program

Abstract: Most primary care physicians do not treat obesity, citing lack of time, resources, insurance reimbursement, and knowledge of effective interventions as significant barriers. To address this need, a 10‐minute intervention delivered by the primary care physician was coupled with individual dietary counseling sessions delivered by a registered dietitian via telephone with an automated calling system (House‐Calls, Mobile, AL). Patients were seen for follow‐up by their physician at weeks 4, 12, 24, 36 and 52. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(63 citation statements)
references
References 23 publications
(24 reference statements)
0
63
0
Order By: Relevance
“…Studies have shown that professional advice and followup with obese patients influence their motivation to make changes in diet and exercise and may promote successful weight loss. 20,21,[36][37][38][39][40] There is a need for reimbursement mechanisms that allow providers to give their patients sufficient weight reduction counseling and that link this counseling with reimbursement for intensive, evidence-based, behavioral interventions to lose weight. 28,34 Also, training in nutrition and exercise guidelines would give physicians a foundation for and perhaps a greater disposition toward addressing these problems with patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that professional advice and followup with obese patients influence their motivation to make changes in diet and exercise and may promote successful weight loss. 20,21,[36][37][38][39][40] There is a need for reimbursement mechanisms that allow providers to give their patients sufficient weight reduction counseling and that link this counseling with reimbursement for intensive, evidence-based, behavioral interventions to lose weight. 28,34 Also, training in nutrition and exercise guidelines would give physicians a foundation for and perhaps a greater disposition toward addressing these problems with patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, studies reveal that patients counseled regarding their weight or strategies for improving diet and exercise are substantially more likely to report that they are working on these areas, 20,21,36,37 and may be more likely to lose weight. 37,38 Finally, a review of randomized control trials indicates that coordination of weight loss efforts with a health professional may result in greater success among overweight or obese patients. 39 The U.S. Preventive Services Task Force recently concluded that there is some evidence that high-intensity counseling about diet, exercise, or both in conjunction with behavioral interventions produces modest, sustained weight loss in adults who are obese.…”
mentioning
confidence: 99%
“…[2][3][4][5] Calorie restriction, without malnutrition of essential nutrients, may also improve mitochondria efficiency and reduce oxidative stress in association with decreases in DNA damage and 24-hour energy expenditure. 6,7,12,45 As shown previously for other commercially available meal 12 NutriSystem (Fort Washington, PA), 13 Healthy Solutions (Health Management Resources® Corporation (HMR), Boston, MA), 14 Standard Process (Palmyra, WI), 15 and Ultra-Slim Fast (Unilever Bestfoods, Englewood Cliffs, NJ), 46 the Isagenix 28-day program is an effective and safe weight loss program. Increasing the number of evidence-based weight management interventions available to clinicians for disease prevention is important to address the individualized eating habits of patients and the constraints of time, knowledge, and costs of the providing clinicians.…”
Section: Discussionmentioning
confidence: 67%
“…19 Until recently, Medicare, Medicaid and major health insurance companies did not officially considered obesity as a disease and do not generally reimburse for obesity treatment, unless related comorbidities exist. 20,21 Also, before strong evidence from large prospective studies controlling for several potential confounders showed a solid and independent association between obesity and cardiovascular disease, there was major controversy on whether or not obesity was related to atherosclerosis. 22,23 Moreover, the Framingham risk score, one of the most widely used methods for estimating cardiovascular risk, does not include obesity in the equation.…”
Section: Discussionmentioning
confidence: 99%